The Influence of Price Fairness and Service Quality on Customer Loyalty at Alfamart Gorontalo - Fritania Bonde Fitriana; Cindy Pratiwi Julyani Daud; Hapsawati Taan; Melan Angriani Asnawi; Ramlan Amir Isa (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study investigates the effects of price fairness and service quality on customer loyalty at Alfamart stores in Gorontalo City. The research is motivated by the rapid growth of the modern retail industry and increasing market competition, which require retailers to strengthen customer loyalty through fair pricing practices and superior service delivery. A quantitative approach with a causal associative design was employed. Data were collected from 96 Alfamart customers selected through purposive sampling based on the Lemeshow formula. A structured questionnaire using a five-point Likert scale was administered, and the data were analyzed using multiple linear regression. Classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests, were conducted to ensure model validity. Hypothesis testing was performed using t-tests and F-tests, while the coefficient of determination (R²) was used to assess explanatory power. The results indicate that price fairness has a positive and significant effect on customer loyalty (t = 4.629; p < 0.001). Service quality also positively and significantly influences customer loyalty (t = 4.710; p < 0.001). Furthermore, price fairness and service quality simultaneously exert a significant positive effect on customer loyalty (F = 47.382; p < 0.001). The coefficient of determination (R² = 0.511) reveals that both variables explain 51.1% of the variation in customer loyalty. Service quality emerged as the more dominant predictor. These findings suggest that integrating fair pricing strategies with continuous service quality improvement is essential for enhancing customer loyalty and sustaining competitiveness in the modern retail sector.